Strategi Pembelajaran Guru Pendidikan Agama Islam Dalam Meningkatkan Akhlakul Karimah Peserta Didik Di SMPIT Asy-Syukriyyah Kota Tangerang - Haryanti, Irma; Ubaidillah Al Alghifary S, Muh.; Widyastri, Sri (CV. Multi Kreasi Media, 2024)
The purpose of this study was to describe the morals learning program for students at SMPIT Asy-Syukriyyah Tangerang, to analyze the learning strategies of PAI teachers in increasing the students' morals at SMPIT, and to describe the supporting and inhibiting factors in implementing PAI teacher learning strategies in increasing the students' morals. studied at the SMPIT. This study uses qualitative methods with data collection techniques through observation, interviews, and documentation. And data analysis techniques by doing data reduction, data presentation, and drawing conclusions and verification. The results of this study indicate that 1). the moral learning program for students at SMPIT Asy-Syukriyyah Tangerang is Faith and Taqwa Development Night (MABIT), Islamic Personal Development (BPI) for students, periodic teacher debriefing and teacher Islamic Personal Development (BPI), congregational prayers, and practice habits worship., 2). The learning strategy for PAI teachers in increasing the akhlakul karimah of students at SMPIT Asy-Syukriyyah Tangerang is by providing examples/examples, varied teaching methods, and collaborating with parents of students, and 3) Supporting factors in implementing PAI teacher learning strategies in improving Akhlakul Karimah students at SMPIT Asy-Syukriyyah Tangerang are parents who don't care about children's development, students with problems, gadgets, and an unsupportive environment. The inhibiting factors are parents who don't care about children's development, students with problems, gadgets, and an environment that doesn't support them.